Mannose-binding lectin gene codon 54 polymorphism susceptible to brucellosis in Turkish children - Bayram, Nuri; Özkınay, Ferda; Onay, Hüseyin; Yılmaz-Çiftdoğan, Dilek; Tufan, Senem; Vardar, Fadil (The Turkish Journal of Pediatrics, 2012)
Genetic factors are as important as environmental factors in susceptibility to brucellosis. Among these genetic factors, mannose-binding lectin (MBL) deficiency contributes to susceptibility to animal brucellosis. The aim of the study is to determine the influence of codon 54 polymorphisms in the MBL gene on susceptibility to brucellosis. Forty-three patients diagnosed with brucellosis and 106 healthy children were admitted in the study. In the patient group, 19 (44.2%) subjects had AA, 22 (51.1%) subjects had AB and 2 (4.6%) subjects had BB genotypes for codon 54 polymorphism. Eighty-two (77.4%) of the healthy children had AA genotype, while 24 (22.6%) had AB genotype. Our results revealed that genotype frequencies carrying MBL variant allele at codon 54 among the patients were significantly higher compared to those found in the control group (55.8% and 22.6%, respectively; p = 0.0001, odds ratio [OR] = 4.316, 95% confidence interval [CI]: 2.030-9.177). Our data suggest that children with MBL codon 54 AB or BB genotype are more susceptible to brucellosis.